Dipeptides in CSF and plasma: diagnostic and therapeutic potential in neurological diseases - Katharina Küper; Gernot Poschet; Julia Rossmann; Sven F. Garbade; Alexander Spiegelhalter; Dan Wen; Georg F. Hoffmann; Claus P. Schmitt; Thomas Opladen; Verena Peters (Amino Acids)
Abstract Dipeptides (DPs), composed of two amino acids (AAs), hold significant therapeutic potential but remain underexplored. Given the crucial role of AAs in central nervous system (CNS) function, this study investigated the presence of DPs in cerebrospinal fluid (CSF) and their correlation with corresponding AAs, potentially indicating their role as AA donors. Plasma and CSF samples were collected from 43 children with neurological or metabolic conditions of unknown origin, including 23 with epilepsy. A panel of 33 DPs was quantified using UPLC-MS/MS. Out of 33 DPs, 18 were detectable in CSF and 20 in plasma, displaying high inter-individual variance. Gly-Asp, Gly-Pro, and Ala-Glu were consistently found in all CSF samples, while only Gly-Asp was universally detectable in plasma. Anserine and carnosine were prominent in CSF and plasma, respectively, with no other histidine-containing DPs observed. Generally, DP concentrations were higher in plasma than in CSF; however, anserine and Gly-Pro had similar concentrations in both fluids. Significant correlations were observed between specific DPs and their corresponding AAs in CSF (Gly-Glu, Gly-Pro and Ser-Gln) and plasma (Glu-Glu and Glu-Ser). Notably, patients with epilepsy had elevated medium anserine concentrations in CSF. This study is the first to demonstrate the presence of numerous DPs in CSF and plasma. Further research is needed to determine if DP patterns can support the diagnosis of neurological diseases and whether DP administration can modulate amino acid availability in the brain, potentially offering new therapeutic options, such as for defects in the amino acid transporter.